GAMBARAN PEMERIKSAAN INSPEKSI VISUAL ASETAT SEBAGAI DETEKSI LESI PRAKANKER SERVIKS PADA WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT X KECAMATAN MARPOYAN DAMAI PEKANBARU - Dyah Astrid Astrid; Wiwit Ade Fidiawati; Amru Sofian (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is the second most common cancer in women inIndonesia. Early detection of cervical cancer with Visual Inspection with AceticAcid (VIA) is an alternative method that recommended for developing countrysuch as Indonesia. Indirect female sex workers have a higher risk of cervicalcancer. The aim of this study is to describe the characteristic of respondent and todetect dysplastic cervical epithelial cells with VIA. The method of this research isdescriptive observational. The study population was all indirect female sexworkers at hotspot X District Marpoyan Damai Pekanbaru and the samples weretaken with total sampling method. The result showed that among 33 sample, 14people (42%) were diagnosed with positive white appearance (positive VIA).Keywords: Visual inspection with acetic acid, Cervical cancer, Cervicalprecancerous lesion, Indirect Female Sex Workers